Exploring usage patterns and safety perceptions of the users of electric three-wheeled paratransit in Patna, India. Issue 1 (March 2020) - Priye, Shiv; Manoj, M.
Highlights: Investigates the travel patterns of three-wheeled electric rickshaw users. Students are more likely to continue the use of electric rickshaws. Electric rickshaw replaces a majority of trips made on conventional (gasoline-based) auto-rickshaws. Perceptions of vehicle safety is related to future use of electric rickshaws. Abstract: Electric three-wheelers (popularly known as electric rickshaws) are battery-powered vehicles that have emerged in many Indian cities as an environment-friendly and energy-efficient paratransit mode of transport. The government of India is developing policies for the broader adoption of the mode to promote sustainable mobility and accessibility. While many Indian cities have been operating electric rickshaws, little is documented about the usage patterns of this mode. An investigation into the usage patterns and safety perceptions of the riders would provide essential inputs to the planning and design of electric rickshaw services for a city. Using a primary data collected from Patna, India, the study explores the travel patterns and safety perceptions of electric rickshaw riders. Statistical models were developed to investigate the effects of socio-demographics and travel context attributes on trip rate, mode replacement and continuation of the use of electric rickshaws in the future. The analysis reveals that electric rickshaws replace a majority of trips made on conventional (gasoline-based) auto-rickshaws. It is found that electric rickshaw is a popular mode choice for educational—and shopping-related trips and students are the frequent users. Further, to identify the most relevant safety issues related to electric rickshaws, grey relation analysis (GRA) was applied to the scaled items. The results disclose that the users are highly concerned over the light body, solid covers and railings, and about the rear-end protection of the electric rickshaws. The on-board safety of small children is also of high concerns. Individuals who opine that electric rickshaws require rear-end protection or need solid covers and railings will be less likely to use this mode in the future. Further, females are less likely to continue the use whereas students would use electric rickshaws in the future, all else being equal. The findings of the study would help develop plans and policies for the improvement of electric rickshaw services to have a sustainable public transportation system that is less dependent on conventional fuels.